2015
DOI: 10.1681/asn.2014060546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Risk of ESRD in the Urban Poor

Abstract: The capacity of risk prediction to guide management of CKD in underserved health settings is unknown. We conducted a retrospective cohort study of 28,779 adults with nondialysis-requiring CKD who received health care in two large safety net health systems during 1996-2009 and were followed for ESRD through September of 2011. We developed and evaluated the performance of ESRD risk prediction models using recently proposed criteria designed to inform population health approaches to disease management: proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Chronic kidney disease (CKD) is a national and international public health problem characterised by a slow loss of kidney function over time, and between 23 and 26 million people in the United States have CKD (Coresh et al ; Levey et al ). Commonly recognised risk factors for the development and progression of CKD include diabetes, hypertension, cardiovascular disease, older age, higher body mass index and being African American (Maziarz et al ; United States Renal Data System [USRDS] ). Preserving kidney function and slowing progression of CKD require self‐management behaviours that include adherence to pharmacological therapy, avoidance of non‐steroidal anti‐inflammatory drugs (NSAIDS), diet modifications, glycemic control, regular exercise, blood pressure control and tobacco avoidance (Tuot et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a national and international public health problem characterised by a slow loss of kidney function over time, and between 23 and 26 million people in the United States have CKD (Coresh et al ; Levey et al ). Commonly recognised risk factors for the development and progression of CKD include diabetes, hypertension, cardiovascular disease, older age, higher body mass index and being African American (Maziarz et al ; United States Renal Data System [USRDS] ). Preserving kidney function and slowing progression of CKD require self‐management behaviours that include adherence to pharmacological therapy, avoidance of non‐steroidal anti‐inflammatory drugs (NSAIDS), diet modifications, glycemic control, regular exercise, blood pressure control and tobacco avoidance (Tuot et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Complementary studies in large study cohorts have yielded additional risk predictive models for ESRD which are intended for use by clinicians to estimate individual patient- rather than population-level risk [ 25 , 26 ]. Using criteria (proportion of cases followed and proportion needed to follow) designed to inform population-level disease assessment, we recently observed that a model incorporating age, race, sex, eGFR and dipstick proteinuria adequately predicted progression to ESRD among vulnerable persons with moderate or severe CKD who were identified through systematic review of the EHR [ 18 ]. Our current study findings extend and leverage our prior work, by placing the proportion of cases followed (PCF) and proportion of the population needed to be followed (PNF) more squarely in the context of how clinical care is actually delivered for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, low individual-level provider and patient awareness of CKD have reinforced the need to optimize multi-level strategies (at the community, organization, practice, and patient levels) to help assess and manage CKD [ 18 , 37 41 ]. Our study findings demonstrate the potential usefulness of clinical data from the EHR to provide reliable information for CKD care assessment at the level of the organization and at the level of a disease- or clinic-based practice which might readily generalize to other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations